AUTHENTIC LEADERSHIP AND KNOWLEDGE SHARING IN INDONESIA'S DATA SCIENCE COMMUNITIES: THE MEDIATING ROLE OF ORGANIZATIONAL COMMITMENT - Aldo Lovely Arief Suyoso; Muchammad Toyib; Hendro Margono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to investigate the relationships between authentic leadership, organizational commitment, trust, and knowledge sharing behavior in the context of the workplace. Data were collected from members of the astronomy community in Indonesia involved in the development of community-based astronomy tourism. Multiple linear regression analysis was used to test the relationships between these variables. The results show that authentic leadership has a significant positive relationship with organizational commitment and knowledge sharing behavior, both tacit and explicit. Organizational commitment also mediates the relationship between authentic leadership and knowledge sharing behavior. However, trust does not strengthen the relationship between organizational commitment and knowledge sharing behavior. Managerial implications include the importance of developing authentic leadership and fostering organizational cultures that support employee commitment. Academic implications include supporting theories of authentic leadership and enriching understanding of the mechanisms of mediation and moderation in the relationships among variables. This study provides a significant contribution to understanding the dynamics of workplace relationships and highlights the importance of psychological factors in the development of sustainable organizations.